Estimation of fasting Blood glucose levels by invasive and indigenously developed noninvasive technology and its correlation with the glycated hemoglobin (HbA1c) biomarker in healthy and diabetic subjects - Chowdhury K.Md.; Srivastava A.; Sharma N.; Sharma S. (My University, 2025)
This research article represents the cross sectional study about the fasting glycemic index of normal and hyperglycemic subjects by invasive and indigenously developed noninvasive technology. Moreover, correlation between the fasting glycemic index and glycated hemoglobin (HbA1c) biomarker profile of both the normal and diabetic subjects was analyzed and discussed. The fasting glycemic index measurement was performed by the indigenous developed noninvasive method which utilizes both the amplitude modulated ultrasound and infrared techniques. The standing wave pattern of the ultrasound causes molecular vibration in the focused zone. The infrared light based technology had been utilized to detect those glucose sensitive vibrational patterns to predict the glycemic index of the normal and diabetic subjects. Invasive fasting glycemic index and profile of glycated hemoglobin (HbA1c) biomarker were determined by the established invasive methods. The result emphasizes that both the invasive, noninvasive fasting glycemic index values change as the glycemic index changes. Similarly, the glycated hemoglobin (HbA1c) biomarker profile of the normal subjects varies largely as compared to the diabetic subjects.